Phase and morphology evolution of magnesium niobate powders synthesized by solid-state reaction - Ananta S. (2014)
Magnesium niobate (MgNb2O6; MN) powders have been prepared and characterized by TG-DTA, XRD, SEM and EDX techniques. The effect of calcination temperature, dwell time and heating/cooling rates on phase formation, morphology and chemical composition of the powders are examined. The calcination temperature and dwell time have been found to have a pronounced effect on the phase formation of the calcined magnesium niobate powders. It has been found that the minor phases of unreacted MgO and Nb2O 5 phases tend to form together with the columbite-type MgNb 2O6 phase, depending on calcination conditions. It is seen that optimisation of calcination conditions can lead to a single-phase MgNb2O6 in an orthorhombic phase. Higher calcination times and heating/cooling rates clearly favoured particle growth and the formation of large and hard agglomerates. © 2004 Published by Elsevier B.V.